The unappreciated intracellular lifestyle of Blastomyces dermatitidis - Sterkel, Alana (J Immunol, 2015)
Blastomyces dermatitidis, a dimorphic fungus and the causative agent of blastomycosis, is widely considered an extracellular pathogen, with little evidence for a facultative intracellular lifestyle. We infected mice with spores - the infectious particle - via the pulmonary route and studied intracellular residence, transition to pathogenic yeast and replication inside lung cells. Nearly 80% of spores were inside cells at 24 hours after infection with 10(4) spores. The majority of spores were located inside of alveolar macrophages, with smaller numbers in neutrophils and dendritic cells. Real time imaging showed rapid uptake of spores into alveolar macrophages, conversion to yeast, and intracellular multiplication during in vitro co-culture. The finding of multiple yeast in a macrophage was chiefly due to intracellular replication rather than multiple phagocytic events or fusion of macrophages. Depletion of alveolar macrophages curtailed infection in mice infected with spores, and lead to a 26-fold reduction in lung CFU by 6 days post-infection vs. non-depleted mice. Phase transition of the spores to yeast was delayed in these depleted mice over a time frame that correlated with reduced lung CFU. Spores cultured in vitro converted to yeast faster in the presence of macrophages than in medium alone. Thus, while advanced B. dermatitidis infection may exhibit extracellular residence in tissue, early lung infection with infectious spores reveals its unappreciated facultative intracellular lifestyle.